2019
DOI: 10.3390/biom9040144
|View full text |Cite
|
Sign up to set email alerts
|

Host-Microbiome Synergistic Control on Sphingolipid Metabolism by Mechanotransduction in Model Arthritis

Abstract: Chronic inflammatory autoimmune disorders are systemic diseases with increasing incidence and still lack a cure. More recently, attention has been placed in understanding gastrointestinal (GI) dysbiosis and, although important progress has been made in this area, it is currently unclear to what extent microbiome manipulation can be used in the treatment of autoimmune disorders. Via the use of appropriate models, rheumatoid arthritis (RA), a well-known exemplar of such pathologies, can be exploited to shed ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…108 The intracellular level of sphingolipid derivative sphingosine-1-phosphate (SIP) has been correlated to several inflammatory disorders, including RA. 109 Sphingolipid is converted to SIP by sphingosine kinase (Sphk 1/2). 110 Studies have shown that increase in the expression of ERK1/2, Akt, and TLR4 enhances the activity of Sphk1/2 and promotes the intracellular level of SIPs.…”
Section: Intracellular Signaling As Therapeutic Targets Of Ramentioning
confidence: 99%
“…108 The intracellular level of sphingolipid derivative sphingosine-1-phosphate (SIP) has been correlated to several inflammatory disorders, including RA. 109 Sphingolipid is converted to SIP by sphingosine kinase (Sphk 1/2). 110 Studies have shown that increase in the expression of ERK1/2, Akt, and TLR4 enhances the activity of Sphk1/2 and promotes the intracellular level of SIPs.…”
Section: Intracellular Signaling As Therapeutic Targets Of Ramentioning
confidence: 99%
“…The CIA animal model is a common experimental animal model of RA that is established by immunization of animals with type II collagen, and this model has clinical features similar to those of human RA. The interplay between the gut microbiota and inflammatory arthritis in animal models has been demonstrated in vivo [ 82 ]. Previous studies reported that the alteration of the gut microbiota composition marked the preclinical phase of murine CIA and preceded the development of disease [ 83 , 84 ].…”
Section: Gut Microbiota and Metabolites In Ramentioning
confidence: 99%
“…Furthermore, the fecal transplantation from RA patients to germ-free arthritis-prone SKG mice induces the Th17 profile in the gut mucosa and severe RA, and when SKG dendritic cells were cultivated with Prevotella copri , there was an increased IL-17 response to RA autoantigens, suggesting that the gut microbes could induce autoreactive cells in the gut mucosa [14]. Interestingly, although MTX induces a decrease in bloodstream inflammation, MTX-treated CIA mice showed a decrease in microbial diversity, expansion of Prevotella spp., and no association with eubiotic microbiome [15,16].…”
Section: Introductionmentioning
confidence: 99%